Computerized Analysis of Intrapartum Fetal Heart Rate Patterns and Adverse Outcomes in the INFANT Trial. Issue 3 (March 2020) - Steer, P. J.; Kovar, I.; McKenzie, C.; Griffin, M.; Linsell, L.
Abstract : (Abstracted from BJOG 2019;126:1354–1361) During the 1960s and 1970s, intermittent auscultation was replaced by the alternative method of continuous electronic fetal monitoring (EFM) and cardiotocography (electronic monitoring of the fetal heart rate [FHR] and uterine contractions, or CTG). Meta-analyses have reported a 59% drop in intrapartum deaths attributable to hypoxia and a reduced risk of neonatal seizures, but a 2017 Cochrane review concluded that while EFM did reduce the rates of neonatal seizures, it did not provide "clear differences in cerebral palsy, infant mortality, or other standard measures of neonatal well-being." Human error in interpreting the FHR pattern is a possible explanation for the ineffectiveness of EFM.